Investigating The Influences Of Cross Training Configurations In Assembly Lines - Tai, Lee Zhen (2011)
By permitting operators to perform a different part of the organization's work, a cross-training model is developed. Its chief purpose is to promote multi-functionality of operators thus improves workforce flexibility. This research intends to investigate the effect of cross-training configurations, focusing on assembly lines under the influences of operator absenteeism, operator turnover, product changeover and learning. The cross training configurations, specifically Scheduled Rotation, Floating Operators, Zoned Worksharing – Two Skills Chaining, Zoned Worksharing Hierarchical and Craft were experimented.